Rapid Weight Loss of Up to Five Percent of the Body Mass in Less Than 7 Days Does Not Affect Physical Performance in Official Olympic Combat Athletes With Weight Classes: A Systematic Review With Meta-Analysis - Mauricio, Clóvis De Albuquerque; Merino, Pablo; Merlo, Rodrigo; Vargas, José Jairo Narrea; Chávez, Juan Ángel Rodríguez; Pérez, Diego Valenzuela; Aedo-Muñoz, Esteban Ariel; Slimani, Maamer; Brito, Ciro José; Bragazzi, Nicola Luigi; Miarka, Bianca (Frontiers in Physiology, 2022)
Given the relevance of the effects that weight loss can generate on the physical performance in athletes, this work performed a systematic review with meta-analysis of the published literature on rapid weight loss (RWL) and examined its impact on the physical performance in Official Olympic combat sports athletes. The “Preferred Reporting Items for Systematic Reviews and Meta-Analysis” (PRISMA) guidelines were followed to ensure an ethical and complete reporting of the findings. PubMed, SPORT Discus, and EBSCO were the electronic databases explored for article retrieval and selection. The following string was applied: “rapid weight loss” OR “weight loss” OR weight reduction” AND “judo” OR “wrestling” or “taekwondo” or “boxing” AND “performance.” Based on the quality analysis, conducted according to the “Tool for the assessment of study quality and reporting in exercise training studies” (TESTEX), ten articles achieved a score >6 points. The meta-analysis showed a significant difference in pre versus post-weight loss (p=0.003) and no effects in pre versus post power and strength performance analysis (p>0.05 for both results). Based on our systematic review and meta-analysis of the literature, RWL up to ≤5% of the body mass in less than seven days does not influence performance outcomes in Official Olympic combat athletes with weight classes, considering the strength and power measures.